Multimodal management of forgotten encrusted ureteral stents (Journal of Kathmandu Medical College, 2017)
Background: Forgotten ureteral stents are seen in urologic practice because of ignorance of patients or failure of physician to counsel the patients. They can cause significant morbidity and pose a management and legal dilemma.Objectives: To evaluate the effi cacy and feasibility of different endourological approaches like percutaneous nephrolithotomy, ureteroscopic lithotripsy, cystolithotripsy and extracorporeal lithotripsy in the treatment of forgotten encrusted ureteral stents.Methods: Total 10 patients with forgotten encrusted double J stents from January 2013 to Nov 2015 were included. Mean age of the patients was 38.4 years (1.5 -5 years). All patients were evaluated for stent encrustation and associated stone burden by X-ray KUB and Intravenous Urography. Combined endourological procedures like percutaneous nephrolithotomy, ureteroscopic lithotripsy, cystolithotripsy and extracorporeal lithotripsy and even open surgery was done to remove these stents. The patients characteristics, indications for stenting, indwelling time, site of encrustation, hospital stay etc were all noted.Results: Total 10 patients presented with forgotten Double J stents. Out of three patients with large encrustations both in renal pelvis and urinary bladder, one patient underwent percutaneous nephrolithotomy and cystolithotripsy. Rest two patients underwent extracorporeal lithotripsy for two sessions for renal pelvic encrustation and cystolithotripsy for urinary bladder encrustation. Four patients underwent ureteroscopic and cystolithotripsy. Two patients in whom all fractured coils were in urinary bladder, underwent cystolithotripsy. All the stents were removed under C-arm fluoroscopic guidance. In one patient, open ureterotomy was done to remove the knotted stent.Conclusion: The use of Double J stent should be limited. The combination of various endourological techniques and extracorporeal lithotripsy can achieve effective stent and stone treatment with minimal morbidity and hospital stay.Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, page: 116-119